KONSEP DAN MANFAAT PENGATURAN SAHAM TANPA NILAI NOMINAL DALAM PASAR MODAL INDONESIA - Ida Kariahenta Silalahi; Nur Sayidah (Faculty of Law, Universitas Jenderal Soedirman, 2014)
The purpose of this research is to find out the concept and benefit of regulation of no par value shares in Indonesian Capital Market. The legal issue of this research is the philosophical meaning of no par value shares as stipulated in Article 31 subsection (2) of Company Law 2007. Ontologically, regulation of no par value shares is one of alternatives to solve the crisis of capital market. Etiologically, the regulation will give the value of benefits in term of providing easiness to perform corporate action, simplification of accounting, no distinction between issued shares and outstanding shares, the shares price is not determined by the nominal price but the market price, it remains to be traded, the company may still do a rights issue to obtain fresh funds even during crisis and they can use mandatory and optional system.Keywords: regulation, no par value shares, capital market.